If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1X + 4Y = 58 Solving 1X + 4Y = 58 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4Y' to each side of the equation. 1X + 4Y + -4Y = 58 + -4Y Combine like terms: 4Y + -4Y = 0 1X + 0 = 58 + -4Y 1X = 58 + -4Y Divide each side by '1'. X = 58 + -4Y Simplifying X = 58 + -4Y
| -5x-10=-3+2x | | 7(n-4)-(6-3n)=9n | | 0,001*0,001x=1/8 | | 2+3x=-5x-6 | | 2x-5=-2+x | | H=0.001x^2-X+27 | | 12h=72 | | (x+4)+(x+2)+(x+5)=2(x+1)+2(x+3) | | 90m^2+21mn-6n^2=0 | | T-75H=735 | | 9x+7-7x=4+x+5 | | -2=6+2x | | -20=b-5 | | 8-n=6+4n | | -9+7m=1+5m | | (m+2)(m-2)=0 | | 3(5-q)+6=9 | | 5(x+2)-(2x-7)= | | 10g=1100 | | x+4+x+2+x+5=2(x+1)+2(x+3) | | 10=1100 | | 3x-6=-14-7+6x+6 | | m^2-6m-33=-6 | | 5x-2=2x-35 | | 4x=38-2x+8 | | 5n^2-50n+105= | | Gsquared+3g=70 | | -10(-m)= | | b+3a=21 | | -4=6-z-z | | 2(3x+8)+9=7+4x | | 12x-4x^2=-7 |